Seasonal wetlands make a relatively limited contribution to the dissolved carbon pool of a lowland headwater tropical stream - Solano Rivera, Vanessa (2024)
Wetlands process large amounts of carbon (C) that can be exported laterally to streams and rivers. However, our understanding of wetland inputs to streams remains unclear, particularly in tropical systems. Here we estimated the contribution of seasonal wetlands to the C pool of a lowland headwater stream in the Australian tropics. We measured dissolved organic and inorganic C (DOC and DIC) and dissolved gases (carbon dioxide—CO2, methane—CH4) during the wet season along the mainstem and in wetland drains connected to the stream. We also recorded hourly measurements of dissolved CO2 along a ‘stream–wetland drain–stream’ continuum, and used a hydrological model combined with a simple mass balance approach to assess the water, DIC and DOC sources to the stream. Seasonal wetlands contributed ∼15% and ∼16% of the DOC and DIC loads during our synoptic sampling, slightly higher than the percent area (∼9%) they occupy in the catchment. The riparian forest (75% of the DOC load) and groundwater inflows (58% of the DIC load) were identified as the main sources of stream DOC and DIC. Seasonal wetlands also contributed marginally to stream CO2 and CH4. Importantly, the rates of stream CO2 emission (1.86 g C s−1) and DOC mineralization (0.33 g C s−1) were much lower than the downstream export of DIC (6.39 g C s−1) and DOC (2.66 g g C s−1). This work highlights the need for further research on the role of riparian corridors as producers and conduits of terrestrial C to tropical streams.